PHYSIOLOGICAL AND SANITARY QUALITY OF SEEDS OF WHEAT CULTIVARS SUBMITTED TO CHEMICAL AND BIOLOGICAL SEED TREATMENTS (Colloquium Agrariae. ISSN: 1809-8215, 2023)
The Brazilian triticulture is marked by the high occurrence of seed-borne diseases, capable of causing damage to grain production. The objective was to evaluate the influence of seed treatments on the physiological and sanitary quality of seeds of wheat cultivars. Seeds of three commercial wheat cultivars (TBIO Sossego, TBIO Sinuelo and TBIO Toruk) and four seed treatments (Control, Chemical, Biological, and Chemical + Biological) were used. The physiological quality of the seeds was determined based on the first count germination tests, germination, quantification number of abnormal seedlings, length of aerial part and radicle, dry mass of the whole seedling, and emergence velocity index (EVI). The sanitary quality was determined through the Blotter test. In general, the chemical treatment associated with the seeds of the TBIO Toruk cultivar provided better physiological and sanitary quality indexes.